2014
DOI: 10.1080/00288330.2013.870220
|View full text |Cite
|
Sign up to set email alerts
|

Gambierdiscuscf.yasumotoi(Dinophyceae) isolated from New Zealand's sub-tropical northern coastal waters

Abstract: A globular form of the epiphytic dinoflagellate genus, Gambierdiscus, was isolated and cultured from Northland, New Zealand. The closest species, based on Bayesian analyses of the large subunit ribosomal DNA (LSU rDNA) D1-D3 and D8-D10 regions, were G. yasumotoi and G. ruetzleri. The thecal plate morphology of the isolate, in particular the small pores and large 2'''' plate, most closely resembled G. yasumotoi. However, the ratios of the cell measurements (depth-to-width 1.3 and lengthto-width 1.4) were more s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 17 publications
0
38
0
Order By: Relevance
“…Records of Gambierdiscus yasumotoi in tropical and sub-tropical regions in the Indian, and Pacific Oceans, both in the northern and southern hemispheres, suggest that this species has a circumglobal distribution in tropical and sub-tropical waters. Interesting is the occurrence of G. yasumotoi in northern New Zealand, reported by Rhodes et al (2014a), as sea surface temperatures (SST) fall well below 15 8C in this region, the lowest thermal limit for any species of Gambierdiscus reported to date (Kibler et al, 2012). However, as noted, the specimens were collected in summer, when SST was 23 8C.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Records of Gambierdiscus yasumotoi in tropical and sub-tropical regions in the Indian, and Pacific Oceans, both in the northern and southern hemispheres, suggest that this species has a circumglobal distribution in tropical and sub-tropical waters. Interesting is the occurrence of G. yasumotoi in northern New Zealand, reported by Rhodes et al (2014a), as sea surface temperatures (SST) fall well below 15 8C in this region, the lowest thermal limit for any species of Gambierdiscus reported to date (Kibler et al, 2012). However, as noted, the specimens were collected in summer, when SST was 23 8C.…”
Section: Discussionmentioning
confidence: 92%
“…4). In addition, the genetic differences between these two species are less than those determined for within-species divergence for other Gambierdiscus species (Nishimura et al, 2013;Rhodes et al, 2014a). Morphological and genetic distances similar to, or even larger than the ones reported between putative species within the G. yasumoti/ruetzleri clade have been described within species of other dinoflagellate genera, such as Coolia (Fraga et al, 2008;Momigliano et al, 2013;Rhodes et al, 2014b) and Amphidinium carterae (Murray et al, 2012).…”
Section: Comparison Between Gambierdiscus Yasumotoi and G Ruetzlerimentioning
confidence: 87%
See 1 more Smart Citation
“…Gambierdiscus cf. yasumotoi is a globular form of Gambierdiscus and was isolated from the Bay of Islands in northeastern New Zealand in recent years (Rhodes et al 2014a) and is also known in the southeast Asia region (Parsons et al 2012). The New Zealand isolate produces MTX-3 analogues.…”
Section: Resultsmentioning
confidence: 98%
“…Sampling in subtropical northern New Zealand waters has confirmed that Fukuyoa is well established in Northland. It has been repeatedly detected in samples collected in the Bay of Islands, at Te Uenga Bay and Motuarohia Island [32,33]. The first isolation was from samples collected in February 2013, when it was reported as Gambierdiscus cf.…”
Section: Species Of Gambierdiscus and Fukuyoa Isolated From New Zealamentioning
confidence: 99%